Facile preparation of N-doped porous carbon matrix with Mo2C / Ni supported for hydrogen evolution. (10th September 2020) - Xu, Yuelong; Wang, Jingyue; Liu, Zhan; Zhai, Zuozhao; Ren, Bin; Dong, Xiaoxi; Miao, Junfeng; Zhang, Lihui; Liu, Zhenfa
Abstract: Electrochemical hydrogen evolution has become a popular way to produce clean energy. Traditional catalysts (e.g. platinum (Pt)) are very expensive and rare; therefore, environmentally friendly and cost-effective catalysts are being widely developed. Here, molybdenum carbide and metallic nickel supported on a N-doped porous carbon matrix are prepared as an electrocatalyst through a one-step hydrothermal method with the addition of melamine, polyvinylpyrrolidone (PVP), pectin, ammonium molybdate and nickel nitrate, and the catalysts exhibit excellent catalytic performance for electrochemical hydrogen evolution. The catalysts created with a carbonization temperature of 1000 °C display a low onset overpotential of 60 mV in an acidic solution with a small Tafel slope of 64 mV dec −1 and low overpotentials of 170 mV and 220 mV in 0.5 M H2 SO4 and 1.0 M KOH, respectively, at 10 mA cm −2 . The obtained catalyst maintains remarkable stability after a 240 h durability test and 10000 cyclic voltammetry cycles. The obtained materials possess excellent catalytic performance for the HER due to the synergistic effect of nickel incorporation into molybdenum carbide and the benefit of the porous N-doped carbon matrix for electron and H∗ transport.